Risk for Cardiovascular Disease and One-Year Mortality in Patients With Chronic Obstructive Pulmonary Disease and Obstructive Sleep Apnea Syndrome Overlap Syndrome - Tang, Manyun; Wang, Yidan; Wang, Mengjie; Tong, Rui; Shi, Tao (Frontiers in Pharmacology, 2021)
Background: Patients with chronic obstructive pulmonary disease (COPD) and obstructive sleep apnea (OSAS) overlap syndrome (OS) are thought to be at increased risk for cardiovascular diseases. Objective: To evaluate the burden of cardiovascular diseases and long-term outcomes in patients with OS. Methods: This was a retrospective cohort study. The prevalence of cardiovascular diseases and one-year mortality were compared among patients diagnosed with OS (OS group), COPD alone (COPD group) and OSAS alone (OSAS group), and Cox proportional hazards models were used to assess independent risk factors for all-cause mortality. Results: Overall, patients with OS were at higher risk for pulmonary hypertension (PH), heart failure and all-cause mortality than patients with COPD or OSAS (all P<0.05). In multivariate Cox regression analysis, the Charlson comorbidity index (CCI) score (adjusted hazard ratio [aHR]: 1.273 [1.050–1.543]; P=0.014), hypertension (aHR: 2.006 [1.005–4.004]; P=0.048), pulmonary thromboembolism (PTE) (aHR: 4.774 [1.335–17.079]; P=0.016) and heart failure (aHR: 3.067 [1.521–6.185]; P=0.002) were found to be independent risk factors for one-year all-cause mortality. Conclusions: Patients with OS had an increased risk for cardiovascular diseases and one-year mortality. More efforts are needed to identify the causal relationship between OS and cardiovascular diseases, promoting risk stratification and the management of these patients.